1994
DOI: 10.1039/c39940002371
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of optically active 5-alkoxyfuran-2(5H)-ones and 5-methoxydihydrofuran-2(3H)-one by chiral inclusion complexation

Abstract: Racemic 5-alkoxyfuran-2(5H)-ones and 5-methoxydihydrofuran-2(3H)-one are resolved by inclusion complexation employing a crystallization or suspension method with tartaric acid-derived chiral hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…This conformation is observed for the other molecular complexes. [1][2][3][4][5][6] Therefore, this rigidity seems to be necessary to include 2S. An intermolecular hydrogen bond is found between the N-atom and the OH in 2S molecules.…”
Section: Crystal Structure Determinationmentioning
confidence: 97%
See 1 more Smart Citation
“…This conformation is observed for the other molecular complexes. [1][2][3][4][5][6] Therefore, this rigidity seems to be necessary to include 2S. An intermolecular hydrogen bond is found between the N-atom and the OH in 2S molecules.…”
Section: Crystal Structure Determinationmentioning
confidence: 97%
“…[1][2][3] However, it is very difficult to predict the structure and function of the optimum host-guest pair, since the capability of optical resolution often significantly depends on a slight difference in the molecular structure of the host and/or guest molecules. [4][5][6] In order to shed light on this problem, it is essential to know the correlation between the conformations of the host and guest molecules and their interactions. It has already been reported that the host molecule worked as a useful chiral shift reagent to measure the optical purity of guest molecules by 1 H-and 13 C-NMR.…”
mentioning
confidence: 99%
“…Chiral 2(5H)-furanones of general formula A have recently emerged as important synthetic intermediates. 1 Since these compounds are available from achiral substrates via several asymmetric synthesis protocols, [2][3][4][5][6] knowledge of their absolute configuration is of primary importance. Recently we have demonstrated that absolute configuration of furanones A can be readily and unequivocally determined from the CD spectrum.…”
mentioning
confidence: 99%
“…When the recrystallization method is used for a complexation of 8a and rac-96b, (-)-96b of 100% ee was obtained in 10% yield. 38 Finally, 96a, 96c-e, and 97 were efficiently resolved by complexation with 8, 9, or 10 in an organic solvent or in a water suspension medium to give (-)-96a (92% ee, 41%), (-)-96c (94% ee, 25%), (+)-96d (90% ee, 46%), (+)-96e (92% ee, 68%), and (-)-97 (96% ee, 50%), respectively, in the optical and chemical yields indicated. .…”
Section: -6 Ketones Esters Lactones and Lactamsmentioning
confidence: 97%
“…16 g, 32%). 38 The host-guest inclusion complexation can also be carried out in a water suspension medium. When a suspension of finely powdered 10a (1.5 g, 1.98 mmol) and rac-96b (0.51 g, 3.98 mmol) in water (10 ml) containing hexadecyltrimethylammonium bromide (0.05 g) as a surfactant was stirred at room temperature for 6 h, a 1:1 inclusion complex of 10a and (+)-96b was formed as crystals, which upon heating in vacuo (220 °C/20 mmHg) gave (+)-96b of 98% ee (0.06 g, 24%).…”
Section: -6 Ketones Esters Lactones and Lactamsmentioning
confidence: 99%